Answer:
f(x) = ![\frac{1}{7}(x+5)(x-1)(x-4)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B7%7D%28x%2B5%29%28x-1%29%28x-4%29)
Step-by-step explanation:
Let the equation of the give cubic function is,
f(x) = p(x - a)(x - b)(x - c)
Here, a, b, c and d are the x-intercepts of the given graph.
Since, x-intercepts given in the graph are x = -5, 1 and 4,
Equation of the curve will be,
f(x) = p(x + 5)(x - 1)(x - 4)
Since, the graph of this function passes through (2, -2) also
-2 = p(2 + 5)(2 - 1)(2 - 4)
-2 = -p(14)
p = ![\frac{2}{14}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B14%7D)
p = ![\frac{1}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B7%7D)
Therefore, equation will be,
f(x) = ![\frac{1}{7}(x+5)(x-1)(x-4)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B7%7D%28x%2B5%29%28x-1%29%28x-4%29)